Nanoteamwork: covalent protein assembly beyond duets towards protein ensembles and orchestras. (June 2018) - Banerjee, Anusuya; Howarth, Mark
Graphical abstract: Highlights: Protein function can be extended by covalently ligating protein modules. Improved tools (e.g. sortase, intein, SpyTag, omniligase) extend ligation potential. Multi-step ligation builds nanoteams for catalysis or control of signalling. Non-covalent assembly is also important via amyloids, VLPs and cellulosomes. Abstract : Biological processes often depend on the harmonious interplay of multiple macromolecules. Biotechnology has had great success in applying and modifying individual components, but the building of multi-component teams is at an early stage. Cells are intelligent in sensing their environment, so manipulating just one signal can limit potency and promote side-effects for therapeutics. Here we critically assess the latest advances in irreversibly connecting individual protein units, through different spontaneous or catalysed reactions. Then we outline efforts to go beyond bipartite assembly, towards multimeric or sequence-programmed architectures. These early steps will be put in context of the enormous opportunities for synthetic protein nanomachines, focusing on catalysis and the control of cell signalling for cancer and the immune system.